PENERAPAN PROSEDUR PENERIMAAN ZAKAT, INFAK DAN SEDEKAH PADA BAZNAS KOTA PONTIANAK - Syaefuloh, Riski Maulana; Rohman, Rohman; Redhea, Yaswinta Ulfa; Fahmi, Muhammad; Yunita, Khristina (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This study aims to describe the application of procedures for receiving zakat, infaq, and alms that have been carried out by BAZNAS Pontianak. This research is a descriptive qualitative research with data collection methods through interviews, observation and documentation. Acceptance of ZIS at BAZNAS Pontianak basically refers to Standard Operating Procedures (SOP). BAZNAS Pontianak has two types of SOPs, namely SOPs for receipt of ZIS funds in the form of cash, bank/e-wallet transfers or goods and SOPs for distribution or utilization of ZIS in the form of petty cash and down payments for work programs. The results of this study indicate that the implementation of the ZIS acceptance procedure carried out by BAZNAS Pontianak complies with the SOP (Standard Operational Procedure) made by the Central BAZNAS. However, BAZNAS Pontianak has not fully implemented the SOP for receiving ZIS in the form of goods.